Diversity of Floricultural Crops traded in Langsa City Aceh Indonesia - Ekariana S Pandia; Farah Diba Shahra; Zill Sekar Gading Fawwaz Sentosa; Mughnita Ayu (Jurnal Biologi Tropis, 2022)
Indonesia is a tropical country that has abundant biodiversity, including floriculture plants. The purpose of this study was to determine the diversity of floricultural plants traded in Langsa City. Determination of the research location by purposive sampling. This research was conducted using survey and interview methods, namely tracing floriculture plant traders in each sub-district of Langsa City. The data obtained were analyzed qualitatively, namely grouping by type (species) and family. The diversity of floricultural plants traded in Langsa City is 234 species belonging to 61 families. In Langsa Baro sub-district there are 109 species and 39 families; Langsa Barat as many as 52 species and 19 families; Langsa Kota as many as 96 species and 37 families; Langsa Lama as many as 26 species and 12 families; Langsa Timur as many as 86 species and 30 families. The Araceae family is the largest family found in all floricultural plants traded in Langsa City, which is as many as 51 species.